The Paradoxical Effect of Inclusive Leadership on Subordinates’ Creativity - Zhu, Jinqiang; Xu, Shiyong; Zhang, Bainan (Frontiers in Psychology, 2020)
Existing studies on the relationship between inclusive leadership and innovative behavior do not present a united picture. Drawing up the antecedent-benefit-cost framework, we tried to explain the contradictory relationships between them based on mediating mechanism. Results showed that inclusive leadership promoted subordinates innovative behavior through enhancing subordinates psychological safety but discouraged subordinates innovative behavior through reducing challenge-related stress. Our findings illustrated the complex mediating process of inclusive leadership’s impact on innovative behavior, presenting a complementary explanation of the contradictory relationships between inclusive leadership and innovative behavior. In addition, we validated antecedent-benefit-cost framework.